PENGARUH PERSEPSI DAN SIKAP LINGKUNGAN KELUARGA TERHADAP KEPRIBADIAN YOSHIO DALAM NOVEL AMURITA KARYA YOSHIMOTO BANANA : SEBUAH KAJIAN PSIKOLOGI SOSIAL - , SEKAR AYU SARASWATI, Drs. Deddy H. Oekon, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis examines the perceptions of family environment on behavior change Yoshio character and influence of the perception ofthe characterâs personality in the novel Yoshimoto Banana's work entitled Amurita. Yoshio described as a figure who has a special ability, where it has an impact onYoshioâs feelings of anxiety and distress. Knowing this, Sakumi and other family members just bring a positive perception of what is experienced by Yoshio. The purpose of this study is to determine what kind of positive perception and attitude raised by Sakumi and other family members and what influences the perception and the attitude of Yoshio's personality. The novel is analyzed using the theory of structuralism to determine the intsinsic element engtanglment in the novel. The theory of developmental psychology is used to known Yoshioâs personality. The theoy of social psychology is used to determine the perception in the family environment toward Yoshioâs behavior and influece of the percption toward Yoshioâs personality. The results revealed that positive perceptions and attitude of Sakumi and family members have an effect to Yoshioâs personality. Yoshioâs Personality initially shut down and it is hard to believe in others and always felt fear because he had special powers. The existence of a positive perception that elicits a positive reaction from Sakumi and family make Yoshio eventually regain confidence in himself and others and can clearly define what he wants.